2020
DOI: 10.1186/s40658-020-00308-9
|View full text |Cite
|
Sign up to set email alerts
|

A head-to-head comparison between two commercial software packages for hybrid dosimetry after peptide receptor radionuclide therapy

Abstract: Background Dosimetry after peptide receptor radionuclide therapy (PRRT) is increasing; however, comparing or pooling of dosimetric results can be challenging since different approaches are used. The aim of this study was to perform a head-to-head comparison of post-PRRT curve fitting and dosimetry obtained from two commercial software Hybrid Viewer Dosimetry and PLANET Dose. Methods Post-therapy imaging included planar scintigraphy at 0.5, 4, 24 and 72 h post-injection of [177Lu]Lu-DOTA-TATE for kinetics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…In a recent study, Huizing et al [16] compared dosimetry results obtained with Hybrid Viewer Dosimetry and PLANET ® Dose in ten patients using hybrid imaging data obtained from 0.5 h to 72 h post-injection of [ 177 Lu] Lu-DOTA-TATE. Although our study also concerned PLANET ® Dose, our reference method was Dosimetry Toolkit ® .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Huizing et al [16] compared dosimetry results obtained with Hybrid Viewer Dosimetry and PLANET ® Dose in ten patients using hybrid imaging data obtained from 0.5 h to 72 h post-injection of [ 177 Lu] Lu-DOTA-TATE. Although our study also concerned PLANET ® Dose, our reference method was Dosimetry Toolkit ® .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that interpatient variability, differences in methodologies, models used for dose assessment, imaging system calibration, time-activity curve fitting, variation in organ volumes, intra-individual size variation, 2D/3D dosimetry approach and the number of imaging time points post-therapy, all are known to induce variations in absorbed dose estimates [31,33,36,47,48,57,58]. The use of various dosimetry software and techniques are also leads to variation in absorbed dose estimates for organs and tissues [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…In order to preserve the experience and data acquired thus far with Dosimetry Toolkit® and OLINDA/EXM® V1.0, we needed to verify that the workstations would yield consistent results. Obviously, this can be achieved only if the same methodology is implemented in both platforms (38). Thus, our study, based on a fully 3D imaging protocol, evaluated dosimetric results obtained with the two dosimetry solutions, rst using a body phantom and then in 21 patients undergoing [177Lu]Lu-DOTA-TATE treatment, representing a total of 40 dosimetry analysis.…”
Section: Discussionmentioning
confidence: 99%